2022
DOI: 10.1093/jee/toac056
|View full text |Cite
|
Sign up to set email alerts
|

What Defines a Host? Oviposition Behavior and Larval Performance of Spodoptera frugiperda (Lepidoptera: Noctuidae) on Five Putative Host Plants

Abstract: When an invasive species first breaches quarantine and establishes in yet another country, it invariably causes consternation for growers, in part because of incomplete understanding of the plants that are at risk. The Fall Armyworm, Spodoptera frugiperda (J.E. Smith) is the most recent example in Australia. The number of plants that this polyphagous noctuid is reported to attack is vast, including many crop species. Consequently, initial reactions from grower industry groups that perceived themselves at risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…In contrast, on a vertical plane, when the corn plant is in the vegetative growth stage, most larvae tend to crawl upward along the stalks and congregate on the upper tissues or reproductive organs of the corn plant. These observations are consistent with the study results of Sparks [ 15 ] and Volp et al [ 46 ]. FAW larvae prefer to feed on the mesophyll of the upper leaves, and when these leaves more fully develop and open, they present the characteristic pattern of paired holes, which is considered a key feature for identifying FAW damage [ 6 , 7 , 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, on a vertical plane, when the corn plant is in the vegetative growth stage, most larvae tend to crawl upward along the stalks and congregate on the upper tissues or reproductive organs of the corn plant. These observations are consistent with the study results of Sparks [ 15 ] and Volp et al [ 46 ]. FAW larvae prefer to feed on the mesophyll of the upper leaves, and when these leaves more fully develop and open, they present the characteristic pattern of paired holes, which is considered a key feature for identifying FAW damage [ 6 , 7 , 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…From a genomic analysis of SNPs and gene sequences of 318 S. frugiperda moths collected from 13 provinces, researchers concluded that the S. frugiperda strain that invaded China was derived from “rice-strain” female parent and “corn-strain” male parent [ 9 , 10 ]. Most field populations have been recorded on maize and other Poaceae, as has been found in Africa [ 11 ], India [ 12 ] and Australia [ 6 ]. Some 83% of FAW moths trapped on Yongxing island had fed on C4 plants such as maize, and not rice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The brightest part of the day is when larvae tend to hide (Rojas et al, 2004). The larvae stage lasts for around 14 days in the summer and 30 days in the cooler months (Volp & Myron, 2022). Typically, pupation occurs in the earth, 2 to 8 cm below the surface.…”
Section: Introductionmentioning
confidence: 99%